Tragic props and cognitive function : aspects of the function of images in thinking - Chaston, Colleen. (Mnemosyne, Supplements, 2010)
By applying aspects of cognitive psychology to a study of three key tragic props, this book examines the importance of visual imagery in ancient Greek tragedy. The shield, the urn and the mask are props which serve as controls for investigating the connection between visual imagery and the spectators' intellectual experience of tragic drama. As vehicles for conceptual change the props point to a function of imagery in problem solving. Connections between the visual and the cognitive in tragedy, particularly through image shape and its potential for various meanings, add a new perspective to scholarship on the role of the visual in ancient performance. These connections also add weight to the importance of imagery in contemporary problem solving and creative thought.